1995
DOI: 10.1017/s030500090000982x
|View full text |Cite
|
Sign up to set email alerts
|

Cross-language synonyms in the lexicons of bilingual infants: one language or two?

Abstract: This study tests the widely-cited claim from Volterra & Taeschner (1978), which is reinforced by Clark's Principle Of Contrast (1987), that young simultaneous bilingual children reject cross-language synonyms in their earliest lexicons. The rejection of translation equivalents is taken by Volterra & Taeschner as support for the idea that the bilingual child possesses a single-language system which includes elements from both languages. We examine first the accuracy of the empirical claim and then its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
169
2
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(186 citation statements)
references
References 19 publications
12
169
2
3
Order By: Relevance
“…In younger children, Pearson, Fernández, and Oller (1995) compared parent reports on the MacArthur Communicative Development Inventories (Fenson et al, 1994) and its Spanish adaptation, the MacArthur Inventario de Desarollo de Habilidades Comunicativas (JacksonMaldonado & Bates, 1988), and found that, among SpanishEnglish bilingual children between the ages of 0;8 (years; months) and 2;6, 70% of their vocabulary was language specific and did not overlap with their other language. These findings are comparable to studies of older bilingual children.…”
Section: Testing Vocabulary Of Bilingual Childrenmentioning
confidence: 99%
“…In younger children, Pearson, Fernández, and Oller (1995) compared parent reports on the MacArthur Communicative Development Inventories (Fenson et al, 1994) and its Spanish adaptation, the MacArthur Inventario de Desarollo de Habilidades Comunicativas (JacksonMaldonado & Bates, 1988), and found that, among SpanishEnglish bilingual children between the ages of 0;8 (years; months) and 2;6, 70% of their vocabulary was language specific and did not overlap with their other language. These findings are comparable to studies of older bilingual children.…”
Section: Testing Vocabulary Of Bilingual Childrenmentioning
confidence: 99%
“…As Pearson, Fernández, and Oller (1995) documented, when considering the "total conceptual vocabulary," that is, the words a child knows in one and/or the other language, bilingual children's skills may equal or exceed that of monolinguals. In some cases, however, that will not be the case, and children might be at a serious disadvantage in one or both languages.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Until very recently, the bulk of the research addressing this question was either observational or correlational in nature. On the basis of such studies, there was general agreement that bilingual and monolingual children pass critical milestones in language acquisition at approximately the same age (Pearson & Fernández 1994;De Houwer 1995;Oller et al 1997;Petitto et al 2001), and that same-aged bilingual and monolingual children have relatively equal sized vocabularies when the vocabularies of both languages is taken into account (Pearson & Fernández 1994;Pearson et al 1995;Petitto et al 2001;Paradis & Nicoladis 2008). Indeed, some reports of early comprehension have found that bilinguals have larger overall vocabularies than same-aged monolingual peers (De Houwer et al 2008).…”
Section: Introductionmentioning
confidence: 99%